PELATIHAN PEMBUATAN HAND SANITIZER UNTUK MENINGKATKAN KETERAMPILAN BINAAN PANTI ASUHAN YAYASAN SITI FATIMAH PANDAAN - Windi Zamrudy; Imron Rosyidi; Heny Dewajani; Noor Isnaini Azkiya (Publisher UPT P2M Politeknik Negeri Malang, 2021)
The Department of Chemical Engineering at the State Polytechnic of Malang in carrying out its function, namely carrying out the Tri Dharma of Higher Education is required to carry out community service through various forms of activity, for this reason, collaboration with the Siti Fatimah Pandaan Orphanage Foundation is carried out. The purpose of this PkM is to provide counseling and understanding of the program which is expected to be a provision for assistants to be independent and can improve students' skills. The PkM program at the Siti Fatimah Pandaan Orphanage Foundation was chosen by considering the efficiency and intensity of program implementation. Aspects of the problems that are resolved in this PkM Program are improving the ability, competence, and understanding of the target audience. This PkM activity consists of several activities, including: 1) Assistance in the manufacture of hand sanitizers, 2) Submission of materials for making hand sanitizers. The results of the PkM showed an increase in participants' knowledge and skills in making hand sanitizers. In addition, increasing understanding of the introduction and application of production management and marketing of hand sanitizers. Furthermore, several PkM achievements that have been achieved include: Articles published in national journals with ISSN, and publication of activities on social media